2020
DOI: 10.1016/j.stemcr.2020.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell RNA-Seq Reveals that CD9 Is a Negative Marker of Glucose-Responsive Pancreatic β-like Cells Derived from Human Pluripotent Stem Cells

Abstract: To date, it remains unclear if there are specific cell-surface markers for purifying glucose-responsive pancreatic b-like cells derived from human pluripotent stem cells (hPSCs). In searching for this, we generated an efficient protocol for differentiating b-like cells from human embryonic stem cells. We performed single-cell RNA sequencing and found that CD9 is a negative cell-surface marker of b-like cells, as most INS + cells are CD9 À. We purified b-like cells for spontaneous formation of islet-like organo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 45 publications
0
35
0
Order By: Relevance
“…Attempts made at expanding the pancreatic progenitor population have found that PDX1 cells generated do not necessarily express NKX6-1 and that pancreatic marker expression varied with passage (44,46). The inverse relationship between proliferation and functional maturation of b-like cells was further supported in a recent study examining the cell surface CD9 marker (52). Depleting the stem cell-derived population of CD9 + b-like cells removed the population of immature b-like cells, leaving cells that demonstrated higher expression of genes associated with b-cell maturity and insulin secretion.…”
Section: Caveats Linked To Promoting Proliferation During Hpsc Differmentioning
confidence: 94%
See 2 more Smart Citations
“…Attempts made at expanding the pancreatic progenitor population have found that PDX1 cells generated do not necessarily express NKX6-1 and that pancreatic marker expression varied with passage (44,46). The inverse relationship between proliferation and functional maturation of b-like cells was further supported in a recent study examining the cell surface CD9 marker (52). Depleting the stem cell-derived population of CD9 + b-like cells removed the population of immature b-like cells, leaving cells that demonstrated higher expression of genes associated with b-cell maturity and insulin secretion.…”
Section: Caveats Linked To Promoting Proliferation During Hpsc Differmentioning
confidence: 94%
“…The end goal of stem cell-derived b-like cell research is to develop a transplantable system of cells that fully replicate b-cell function. Ideal tactics to achieve this would be to optimize current differentiation protocols, such as through manual purification of mature populations or treatments that increase final b-like cells (10,12,41,52,60,61), and to improve in vivo site support for transplanted b-like cells (62)(63)(64). Despite the limitations listed above, expanding b-like cells or their progenitors in vitro still presents a promising strategy to further support these approaches.…”
Section: Potential Strategies and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies on TGF-β signaling in beta cells are needed, but, with respect to the differentiation of highly functional beta cells from stem cells, TGF-β fulfills a dual role, as its inhibition is required at early stages while its signaling is beneficial at late stages. Recently, Yoshihara et al demonstrated that non-canonical WNT4 signaling drives the metabolic maturation of beta-like cells—essential for robust insulin secretion—in large part through the induction of an ERRgamma gene network [ 63 ], while Li et al developed a beta cell differentiation protocol that is based on three previously published protocols [ 52 , 53 , 64 ] to obtain beta cells with high glucose-responsiveness and insulin production [ 65 ].…”
Section: Current Status Of Human Esc and Ipsc Differentiation Protmentioning
confidence: 99%
“…Sorting strategies while using a GFP reporter under the control of the insulin gene promoter or an antibody to the beta cell surface marker CD49a enabled obtaining 80–90% pure beta cells [ 57 , 66 ]. Alternatively, the cell-surface marker CD9 can be exploited for negative selection to enrich for glucose-responsive human beta-like cells [ 65 ]. These strategies may also prove to be useful for sorting other hormone-producing cells, such as alpha cells, which contribute to disease etiology by elevating blood glucose levels [ 67 , 68 , 69 ].…”
Section: Current Status Of Human Esc and Ipsc Differentiation Protmentioning
confidence: 99%